(untitled) (The Research of Medical Science Review, 2025)
Rhinoliths are rare calcified masses (Author1 et al., Year) that form within the nasal cavity. This case report presents an uncommon instance of rhinolith in a young female, marking the second reported case in the Maldives within a two-year period. The patient presented with intermittent epistaxis and unilateral nasal obstruction. Diagnosis was confirmed via anterior rhinoscopy, which revealed a rough, yellowish, stony-hard mass located between the middle and superior turbinates in the right nasal cavity. The rhinolith was successfully removed under general anesthesia using an endoscopic procedure, with the largest fragment measuring 2 cm × 1.5 cm. Post-removal follow-up demonstrated significant symptomatic improvement, and the patient expressed high satisfaction with her relief. This case emphasizes that rhinoliths are not limited to older adults and children but can also develop in young adult (Author2 et al., Year), highlighting the importance of careful evaluation in patients with a long-term history of unilateral nasal bleeding and obstruction.